Análisis crítico del proyecto "Apoyo para la Erradicación del Trabajo infantil en el sur de Quito, ejecutado por la fundación Tierra Nueva - Yanza Cruz, Amparo Esmeralda (2014)
This research was conducted in the Tierra Nueva Foundation, the proteject “Suport for the Elimination of Child Labour”, which runs in South Quito, covering 13 districts, coverage is 350 children and adolescents, is funded by the Ministry of Economic and social inclusion, the purpose of the research was to conduct a critical analysis of tjecta general and specific knoeledge of the foundation was held, a generalanalysis of the socio – economic and family of project participants as well as some interviews and lifestories